A new switching control for finite-time synchronization of memristor-based recurrent neural networks. (February 2017) - Gao, Jie; Zhu, Peiyong; Alsaedi, Ahmed; Alsaadi, Fuad E.; Hayat, Tasawar
Abstract: In this paper, finite-time synchronization (FTS) of memristor-based recurrent neural networks (MNNs) with time-varying delays is investigated by designing a new switching controller. First, by using the differential inclusions theory and set-valued maps, sufficient conditions to ensure FTS of MNNs are obtained under the two cases of 0 < α < 1 and α = 0, and it is derived that α = 0 is the critical value of 0 < α < 1 . Next, it is discussed deeply on the relation between the parameter α and the synchronization time. Then, a new controller with a switching parameter α is designed which can shorten the synchronization time. Finally, some numerical simulation examples are provided to illustrate the effectiveness of the proposed results.